2014
DOI: 10.1074/jbc.m114.589747
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Excision Repair-dependent DNA Double-strand Break Formation and ATM Signaling Activation in Mammalian Quiescent Cells

Abstract: Background:In quiescent human cells, UV induces histone H2AX phosphorylation by ATR in a nucleotide excision repair (NER)-dependent manner. Results: UV also activates ATM in response to NER-mediated DNA double-strand break (DSB). Conclusion:The NER reaction in quiescent cells potentially generates multiple types of secondary DNA damage. Significance: This work highlights the importance of our understanding of the DNA damage response in quiescent cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 38 publications
4
58
0
Order By: Relevance
“…However, CHK1 protein levels were nearly absent in the noncycling cells (Fig. 1A), consistent with previous reports in other cell lines (29,32). Nonetheless, this difference in phosphorylation between cycling and non-cycling cells (Fig.…”
Section: Uv-induced Dna Damage Signaling Exhibit Different Profiles Isupporting
confidence: 82%
See 4 more Smart Citations
“…However, CHK1 protein levels were nearly absent in the noncycling cells (Fig. 1A), consistent with previous reports in other cell lines (29,32). Nonetheless, this difference in phosphorylation between cycling and non-cycling cells (Fig.…”
Section: Uv-induced Dna Damage Signaling Exhibit Different Profiles Isupporting
confidence: 82%
“…ATM and ATR Both Contribute to Canonical DNA Damage Signaling Events in UV-irradiated Non-cycling Cells-A recent study found that UV irradiation of non-cycling cells leads to formation of double-strand breaks in DNA in a nucleotide excision repair-dependent manner (29). This double-strand break response was associated with the activation of ATM and the phosphorylation of both H2AX and the more specific ATM substrate CHK2.…”
Section: Atr Contributes To Dna Damage Response Protein Phosphorylatimentioning
confidence: 99%
See 3 more Smart Citations